Namibian-German Diplomacy in colonial reparations (2011 – 2021) - Bimasatria, Narashangsa; Nuraeni, Nuraeni (Masyarakat, Kebudayaan dan Politik, 2024)
Namibia’s history as a German Empire “mandate” from the 1884-1885 Berlin Conference builds a diplomatic relation characterized by the push for reparations. This research aims to study the Namibian-German diplomacy in colonial reparations as a best practice basis in navigating the complex relationship between an ex-colony and its ex-colonizer to achieve reconciliation, particularly between 2011 – 2021 where reparations between the two countries showed concrete progress. Using qualitative methods, this research is guided by the Van Boven Bassiouni principles, the Abuja Proclamation, and Paulose & Rogo’s idea to dissect colonial reparations and McDonald’s multitrack diplomacy as a conceptual framework. This research found that aspirations and legal pushes from the Herero People’s Reparation Corporation triggered the diplomatic processes. Concrete progress started occurring in 2011 with the repatriation of Herero remains to Namibia, followed by recognition of German colonial practices, compensations, and rehabilitative efforts involving various actors. This showcases diplomacy as a relevant approach to resolving colonial reparations, where in the Namibian-German context, the government track emerges as the main track providing the most comprehensive result. This research also highlighted the importance of diplomatic engagement in addressing colonial reparations and its potential to offer a model for achieving reconciliation through restoring human values.